Transformation of Professional Psychosocial Competencies in Crisis Conditions: The work was supported by the Science Committee of RA, in the frames of the research project # 21T-5A044 - Sargsyan, Diana; Papoyan, Varduhi; Galstyan , Alina (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The existing professional competencies in the Republic of Armenia, fixed by educational programs, need to be transformed and supplemented. This need is caused by the crisis situations faced by humanity: the restrictions caused by COVID-19, the post-war psychological and social consequences, the saturated technological requirements for the educational process, etc. The article presents a description of a three-level model of professional psychological and social competencies. This will help to systematize the path of becoming a specialist from personal growth to professionalism in a new way. The model includes upper, middle and lower levels. The upper level includes research, organizational, teaching and technological skills. At the middle level, the activity of a specialist, focus on business, external and internal motivation are represented, at the lower level - emotional, behavioral and volitional qualities. We conducted a primary monitoring of professional psychological and social competencies for professions in demand in recent years in our country (in particular, doctors, psychologists, teachers, military).